2013
DOI: 10.1021/la404312x
|View full text |Cite
|
Sign up to set email alerts
|

Near-Edge X-ray Absorption Fine Structure Studies of Electrospun Poly(dimethylsiloxane)/Poly(methyl methacrylate)/Multiwall Carbon Nanotube Composites

Abstract: This work describes the near conduction band edge structure of electrospun mats of MWCNT-PDMS-PMMA by near edge X-Ray absorption fine structure (NEXAFS) spectroscopy. Effects of adding nanofillers of different sizes were addressed. Despite observed morphological variations and inhomogeneous carbon nanotube distribution, spun mats appeared homogeneous under NEXAFS analysis. Spectra revealed differences in emissions from glancing and normal spectra; which may evidence phase separation within the bulk of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…However, for this system, alignment has been thoroughly discussed in early works through synchrotron spectroscopies. Dichroic ratio studies suggested that macromolecules did not align, which is consistent with the referred works, since no additional electric field was used upon collection …”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…However, for this system, alignment has been thoroughly discussed in early works through synchrotron spectroscopies. Dichroic ratio studies suggested that macromolecules did not align, which is consistent with the referred works, since no additional electric field was used upon collection …”
Section: Resultssupporting
confidence: 86%
“…In fact, on those earlier reports, we have discussed the impact that electrospinning bears on both CNT alignment and bonding dynamics . Indeed, electrospinning has proved successful in the promotion of dispersion and alignment of CNTs in polymeric composites.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The dependence of the intensity of the detected spectral features on the orientation of the final state orbital with respect to the electric field vector of the incident photon beam 58 also allows the surface molecular orientation of nanomaterials [59][60][61] and adsorbates 62 to be investigated.…”
Section: Introductionmentioning
confidence: 99%